Analisis Maslahah dalam Konsep Perwalian Pernikahan Anak Luar Nikah Berdasarkan Kompilasi Hukum Islam - Ahmad Muhammad Mustain Nasoha; Romdhoni, Arif; Sadam Agustin Dwi Ardiyan; Ashfiya Nur Atqiya (El-Faqih : Jurnal Pemikiran dan Hukum Islam, 2024)
This research examines Maslahah in the concept of Islamic law. In the context of guardianship of children out of wedlock in a marriage bond according to the compilation of Islamic law, the substance of this maslahah is very relevant. However, sometimes situations where a child is born outside of marriage can occur. The research method used is Normative/Doctrinal/Literature Research The findings of this study indicate that the concept of guardianship of children out of wedlock in the perspective of the Islamic compilation has been listed in Law No. 1 of 1974 concerning marriage, Article 19 of the Compilation of Islamic Law, Article 53 paragraph 3 of the Compilation of Islamic Law, and Article 75 letter (b) of the Compilation of Islamic Law. That maslahah plays an important role in determining the view of Islamic law on this issue. In this context, it is found that a proper understanding of maslahah, which includes the protection of individual rights and the welfare of society, is essential in dealing with the guardianship of out-of-wedlock children. In this scientific work, several important aspects related to the concept of guardianship of extra-marital children have been discussed. Firstly, there are differences of opinion among scholars regarding the halal or haram guardianship of out-of-wedlock children, Secondly, the importance of paying attention to the values and principles of Islamic law underlying the concept of guardianship of out-of-wedlock children. Third, the a need for a clear and effective regulatory framework to regulate the practice of guardianship of out-of-wedlock children.